The meaning of marriage : facing the complexities of commitment with the wisdom of God - Keller, Timothy, 1950- (Dutton, Penguin Group (USA), 2011)
Based on the sermon series by New York Times bestselling author Timothy Keller, this book shows everyone -- Christians, skeptics, singles, long-time married couples, and those about to be engaged -- the vision of what marriage should be according to the Bible.